PEMANFAATAN MEDIA SOSIAL DALAM EVALUASI PEMBELAJARAN DI PESANTREN JAGAT ‘ARSY - Zulfahmi Zulfahmi (Management of Education: Jurnal Manajemen Pendidikan Islam, 2022)
This research aims to describe the development of rubrics in learning evaluation using social media. The assessment is not only related to cognitive, psychomotor knowledge but also the affective domain and even covers all aspects of mental, psychological and religious spiritual life. In evaluating there are many techniques that can be chosen and carried out by teachers or educators. In the evaluation process, educators carry out evaluation procedures such as evaluation planning, monitoring, reporting and utilization of evaluation results. The research method used is descriptive qualitative by describing phenomena and existing literature. The results of the study show that the learning evaluation rubric using social media is quite effective and has been successfully implemented at the Jagat Arsy Islamic Boarding School. The evaluation approach is carried out using product, project and performance-based assessments, not only answering cognitive questions. The era of digitalization and advances in IT technology are important factors in supporting the development of IT-based evaluation at the Jagat Arsy Islamic Boarding School.